Analisis Kinerja Lurah terhadap Pembangunan Daerah dan Otonomi Daerah di Kelurahan Binaraga, Kecamatan Rantau Utara, Kabupaten Labuhanbatu - Hidayat, Ade; Pohan, Malvira; Latifah Hanum, Sayidah; Kemala Dewi, Putri (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The purpose of this research was to describe how the ward Binaraga , Rantau Utara Subdistrict, Labuhan Batu regency carries out the duties as outlined in government regulation Number 73 of 2005 concerning sub-districts related to tasks that should be carried out by the government, namely (a). implementation of sub-district government activities; (b). community empowerment; (c). Community service; (d). implementation of peace and general agreement; (e). maintenance of public service infrastructure and facilities; and (P). This research uses a qualitative approach with data collection techniques of interviews, observation, document review. The object studied is the performance of the village head towards regional development and regional autonomy. Based on this research, the task that has been fully carried out effectively is the community service task in the area of ​​improving stabilizer infrastructure. Meanwhile, the assistance tasks are the same, but the PKH and BLT programs have not been fully implemented fairly, where when the assistance is distributed there is still a wrong target